Evaluasi Infrastruktur TI Menggunakan Framework COBIT 4.1 (Studi kasus : Sistem Informasi Ujian Online Universitas Y) - Dwiyono Ariyadi (Universitas Darussalam Gontor, 2017)
Use of information technology facility as supporting support vision mission university need to be proven to prove, only with any of the measurement. Infrastructure audit of information technology on online test information system (SIUJO) faculty of technique is a form of measurement the maturity level in formation technology which the purpose is identifying the early possible risk so the process of faculty's bussiness is not trouble. Doing infrastructure audit of information technology using framework cobit 4.1 focus on subdomain AI3 and AI5 with respondent according to RACI. Audit of information technology infrastructure SIUJO shows the result that the maturity level is still on the current level 1. It is necessary for gradual improvement efforts between three years to maturity level 3 to 4. By doing audit earlierly, bussiness process expected to support the faculty.